2021
DOI: 10.21123/bsj.2021.18.2.0217
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of intestinal parasitic infections among random samples at Al- Aziziyah hospital in Wasit province/Iraq

Abstract: The study is designed to identify intestinal parasitic infections examined at Al-Aziziyah Hospital in Wasit Governorate in Iraq. In this study, a total of (460) internal and external patients were monitored for intestinal parasitic infections. All stool samples were analyzed by the direct method (microscopic exam.) to discover the trophozoite stages and cyst stages for intestinal protozoan parasites. The most incidence parasites in different sex, area residence and different age groups. Out of ( 460) patient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Our results showed that male children (3-7 years old) of rural areas are more positivity than other opposite groups of risk factors; which similarly to those observed by other researchers [12,15,21], but in contrast to those reported by others [11,24,28]. This variation might be attributed to method and criteria of sampling, differences in environmental and socio-ecological conditions, as well as health status and level of immunity of participants.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results showed that male children (3-7 years old) of rural areas are more positivity than other opposite groups of risk factors; which similarly to those observed by other researchers [12,15,21], but in contrast to those reported by others [11,24,28]. This variation might be attributed to method and criteria of sampling, differences in environmental and socio-ecological conditions, as well as health status and level of immunity of participants.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, traditional diagnostic methods reported that the prevalence rate of intestinal parasites among the gastrointestinal disordered patients aged ≤20 years was 59.5%. Comparatively, the prevalence rate of IPs in Wasit province 47.7% by Rahi and Majeed [11], 47.17% by Jaffar et al [12], 61.6% by Ahmed et al [15]; whereas in other provinces, there were 55.6% in Sulaimani [20], 89.16% in Baghdad [21], 22.27% in Duhok [22], 18.93% in Karbala [23], and 36.83% in Al-Najaf [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noticed in the table (2 and 3) that the rate of contamination in both sides was high by G. lamblia and E. histolytica, this may be due to the appropriate environmental conditions for developing these phases and this type of parasites which transports by water and food and by the mechanical transporter (flies), or due to shitting near vegetable farms in addition to using stools for fertilizing beside washing vegetables by water contaminated with parasites cysts [20][21][22][23][24] .…”
Section: Resultsmentioning
confidence: 99%